2022
DOI: 10.1186/s12989-022-00495-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced silver nanoparticle-induced pulmonary inflammation in a metabolic syndrome mouse model and resolvin D1 treatment

Abstract: Background Metabolic syndrome (MetS) exacerbates susceptibility to inhalation exposures such as particulate air pollution, however, the mechanisms responsible remain unelucidated. Previously, we determined a MetS mouse model exhibited exacerbated pulmonary inflammation 24 h following AgNP exposure compared to a healthy mouse model. This enhanced response corresponded with reduction of distinct resolution mediators. We hypothesized silver nanoparticle (AgNP) exposure in MetS results in sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Other investigations with the THP-1 monocytic cell line showed no induction of IL-4 production by AgNPs obtained through the reduction of silver nitrate with sodium borohydride [ 85 ]. Furthermore, it was observed that IL-4 production decreased in the lungs of mice that were chronically exposed to AgNPs and had metabolic syndrome [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other investigations with the THP-1 monocytic cell line showed no induction of IL-4 production by AgNPs obtained through the reduction of silver nitrate with sodium borohydride [ 85 ]. Furthermore, it was observed that IL-4 production decreased in the lungs of mice that were chronically exposed to AgNPs and had metabolic syndrome [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…A pathway analysis of 670 ± 49 ng/cm 2 aerosol nAg (14.1 ± 2.3 nm) inhalation exposure to rats after 1 or 7 days enriched the same pathways related to granulocyte and agranulocyte adhesion and diapedesis, IL-10 signaling and hypercytokinemia [ 43 ]. Another study found that 50 μg (20 nm) citrate-coated nAg exposure to mice elevated IL-4 and IL-10 gene expression after 7 days [ 44 ]. Additionally, a study using an in vitro alveolar model composed of an alveolar type-II cell line (A549), differentiated macrophage-like cells (THP-1), mast cells (HMC-1), and endothelial cells (EA.Hy926) found that 0.5 and 5 μg/cm 2 PVP-coated nAg (50 nm) increased the secretion of IL-4, IL-6, and IL-10 after 6 h and 24 h [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In disease environments, including conditions like metabolic syndrome tied to lipid dysregulation, the constitution of macromolecules differs from that in healthy scenarios. Interestingly, it has been observed that the corona around silver nanoparticles in a metabolic syndrome environment can exacerbate inflammatory responses in mice exhibiting metabolic syndromes compared to their healthy counterparts (Alqahtani et al, 2020;Kobos et al, 2020;Alqahtani et al, 2021;Alqahtani et al, 2022). NPs can be transported and internalized into cells either passively or actively.…”
Section: Mechanism Of Microplastic and Nanoplastic Toxicitymentioning
confidence: 99%